تكرٌيس الرقابة الالكترونٌية فًي التشرٌيع الجزائري السوارالالكترونًي نموذجا - حلٌتٌيم مرام - - بن عٌيسى فاطمة (جامعة المسيلة, 2024)
electronic bracelet, is considered one of the new systems that the Algerian legislator recently introduced into the penal policy, stipulated in Law 18-01 dated 12 Jumada al-Awwal 1439 corresponding to January 30, 2018, supplementing Law 05-04 dated 27 Dhu al-Hijjah 1425 corresponding to On February 6, 2005, which includes the Law on the Organization of Prisons and the Social Reintegration of Detainees, which is contained in Chapter Four of Part Six within Articles 150 bis to 150 bis 16 of the Law on the Organization of Prisons, which restricts the freedom of those subject to it by means of modern devices while specifying the spatial space where he may be in , where it is Monitoring the convict remotely using a device mounted on his wrist or the bottom of his foot. Keywords: electronic monitoring, alternative punishments, electronic bracelet, modernization of justice, remote imprisonment.
Keywords: : electronic monitoring; alternative punishments; electronic bracelet; modernization of justice; remote imprisonment.